(untitled) (jornal of the libyan geographical society, 2016)
Electoral geography, which analyzes the spatial patterns of voting processes, has a long history and once held a prominent place in the field of geography. Electoral geographers in the 20th century, from the 1960s through the 1980s, were key practitioners in applying quantitative methods. Mapping was used to analyze and represent election data at both the local and national levels. This work was largely experimental in its scope and focus; however, it did generate... There is a huge body of literature on this subject that has explained the inherent spatial nature of elections, including the process of redrawing electoral districts, the economic and demographic factors affecting them, and the election campaign strategies of parties and candidates.